1984
DOI: 10.1111/j.1365-2222.1984.tb02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐activating factor: a possible mediator of the dual response to allergen?

Abstract: Certain allergic asthmatic patients exhibit a dual response in the lung following bronchial challenge with the appropriate allergen. Often this is paralleled by a cutaneous dual response when the antigen is injected intradermally. The mechanisms underlying such phenomena are not established, bul sonic evidence suggests that the late response is a consequence of the early response. Since platelet activation has been observed following antigen challenge in asthmatic subjects, we have studied the ability of plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Published reports of the responses to intradermal injection of PAF in human volunteers have described acute weal and flare reactions (Basran et al, 1984;Archer et al, 1984). These early effects appear to resolve within 30 to 60 min, and are followed by a secondary response, comprising erythema at the injection site associated with a variable degree of hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Published reports of the responses to intradermal injection of PAF in human volunteers have described acute weal and flare reactions (Basran et al, 1984;Archer et al, 1984). These early effects appear to resolve within 30 to 60 min, and are followed by a secondary response, comprising erythema at the injection site associated with a variable degree of hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…On intradermal injection, Pafacether has been shown to elicit acute extravasation of plasma protein, accompanied by platelet and neutrophil accumulation in the skin of experimental animals Pirotzky et al, 1984). In man, intradermal injection of Paf-acether elicits a biphasic inflammatory response reminiscent of that induced by antigen in suitably sensitized individuals (Archer et al, 1984;Basran et al, 1984). The mechanism of this inflammatory response has not been previously ' characterized.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility has been considered for several years, in view of the high incidence of thromboembolic disease in patients with hypereosinophilia, and the demonstration of PAF in supernatants from stimulated eosinophils was confirmed in later work (Lee et al 1984). However, why eosinophils should make this potent mediator is not clear, but it has been suggested that eosinophil-derived PAF, via its actions on smooth muscle and platelets, might also be involved in the pathogenesis of asthma (Basram et al 1984).…”
mentioning
confidence: 99%